(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Behavioral Activation (BA), although being re-introduced to the community of researchers and clinicians as one of the new third-generation behavioral therapies, has emerged since the 1960s with a long history of research and enhancements. Currently, more than one protocol model of that psychotherapy system coexists. The present article presents an integrative protocol of BA for the treatment of unipolar depression, adopted in the context of clinical school. Three types of depression are presented from their functional conception, as determined by punishment, determined by operant extinction, and determined by non-contingent aversive stimulation. For each type, functional analyzes and interventions based on simple and/or complex activation proposals are presented. Throughout the proposed interventions, integration interfaces with other third generation approaches are also presented, such as Functional Analytical Psychotherapy (FAP) and Acceptance and Commitment Therapy (ACT).